Prescribing pattern of antihypertensive drugs in primary care units in Turkey: results from the TURKSAHA study - (:unkn) unknown (SPRINGER HEIDELBERG, 2007)
Objective The prescribing pattern of drugs used for treating hypertension changes over time in response to changes in recommended guidelines and innovations in drug formulations, among others. In addition, the classes of antihypertensive drugs used vary among the countries. The aim of this study was to investigate the practice of antihypertensive medications in primary care units in Turkey. Methods TURKSAHA is a cross-sectional screening study conducted in 1000 primary care units considered to be representative of primary care in Turkey, with the purpose of defining the demographic characteristics, clinical features, rate of blood pressure control achieved and the antihypertensive drugs prescribed for the hypertensive patients treated in these centers. In this analysis, we investigated the agents used in the treatment regimen. Results Of the 16,270 patients considered to be eligible for inclusion in the study, 15,187 (93.3%) were on an antihypertensive treatment, and 1083 (6.7%) were receiving no treatment. Patients who received treatment but whose antihypertensive medication was not specified (2290 patients) were subsequently excluded, and the trial was carried out with the remaining 12,897 patients. The mean age of the patients was 60 +/- 11 years (60.2% female). Of the 12,897 patients, 75.7% were receiving monotherapy, 19.7% two drugs, 4.1% three drugs and 0.5% four or more drugs. The rate of successful blood pressure control (< 140/90 mmHg; for diabetics < 130/80 mm Hg) in relation to the number of drugs received was 26.3, 25.9, 24.5 and 26.2%, respectively. Among the patients receiving monotherapy, the most frequently used antihypertensive drug class was angiotensin-converting enzyme inhibitors (30.1%), followed by beta-blockers (20.6%), calcium-channel blockers (17.9%), diuretics (15.4%) and angiotensin-receptor blockers (14%). Conclusion As in other European countries, the rate of successful blood pressure control was low among hypertensive patients receiving treatment, and despite the inadequacy of monotherapy to control blood pressure, many of the patients continued this treatment regimen. Consistent with the global trend, the most frequently prescribed anti-hypertensives were angiotensin blockers.
Keywords: angiotensin blockers; antihypertensive medication; TURKSAHA study; HIGH BLOOD-PRESSURE; HYPERTENSION; POPULATION; PREVALENCE; MANAGEMENT; CANADA; TRENDS